A perspective of technology among healthcare provider after the pandemic - Dini, Yunita Arga; Bukuku, Debora (Universitas Muhammadiyah Magelang, 2022)
The rapid spread of the COVID-19 virus has brought about a serious public health emergency on a global scale. There is a considerable need for essential digitally-enabled medical equipment and accessories, as well as for quarantine facilities, surveillance systems, and other related digital technologies. In the fields of healthcare, manufacturing, and education, technologies that facilitate working remotely from safe areas are absolutely necessary. It is possible that digital technology and the tools of Industry 4.0 will be able to satisfy these specific requirements both during and after the COVID-19 crisis. The experts in the healthcare industry can use this perspective to better cope with the difficult times that follow a pandemic. Keywords: Virus infection; COVID-19; Industry development; digital technology; medical care